Si Carancal laban sa mga bongbongeros Carancal against the dinamite pirates - Villanueva, Rene O. (Adventures of Carancal, 2008)
In this story, wherein Carancal fights a band of pirates who use dynamite in fishing, the author gives emphasis to the concern and love for the environment, the riches of the sea. It also highlights the importance of faith and confidence in one's self as well as courage despite personal and/or physical limitations.